Passions and the Principle of Reflection in the Sermons of J. Butler - Mauri, Margarita (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
An important part of the work of Bishop Joseph Butler is focused on the analysis of human nature whose knowledge is of utmost importance for morality. The nature of man, says Butler, is a system or constitution formed, in part, by a set of appetites, passions and affections, and in part by a principle of reflection or conscience with their relationship marked by mutual respect and by the natural superiority of consciousness. Passions, but subject to the rational order, are necessary, are as essential as the proper order. Although man cannot ever reach perfection, when the principle of reflection directs, correcting any excesses of passion, man is virtuous. The article aims to show the basic principles of human nature and explore the role the passions have in it
Keywords: Butler; conscience; passions; affections; human nature